Assessing sustainability of farming systems in mountain agroecosystems of Western Himalaya, India. Issue 7 (9th August 2018) - Negi, Vikram S.; Maikhuri, R.K.; Chandra, A.; Maletha, Ajay; Dhyani, P.P.
ABSTRACT: This paper examines sustainability of cash crops production systems as compared to traditional cereal cropping patterns in terms of their energy efficiency, ecological suitability, economic profitability, and social acceptability. The consistent supply of labor and energy are the most significant requirements for substantial growth of agricultural productivity in Himalayan region. For output–input ratio in terms of monetary efficiency, cash crops performed better (3.16–3.56) as compared to traditional crops (1.57–3.31), whereas the energy output–input ratio of traditional crops was found more efficient (1.63–4.72) as compared to cash crops (1.26–2.36). The monetary input and output analysis of Rabi crops was estimated to be 23.39% and 25.3% of Kharif crops, respectively; Similarly, variance in energy input (27.3%) and output (32.44%) analysis was observed between Rabi and Kharif crops, respectively. Energy input in the form of manure accounted >90% of total energy input, while other inputs (<10%) are contributed in the form of seeds, and animal and human power for all the crops. The study also highlighted the significance of traditional crops and factors responsible for their declining cultivation in the mountain region.